From Being Literate about Health to Becoming Capable of Achieving Health: Health literacy capabilities of Zimbabwean school youth - Martin Micklesson; Tecklah Usai; Dorothy Chinofunga; Emma Oljans (Environmental Association of Southern Africa, 2023)
Food security is an enduring sustainability challenge in the Southern African region. Food availability, accessibility and affordability have profound health impacts and affect the quality of life of a substantial proportion of the world's population. This article aims to explore, together with students in educational settings, questions about the relationships between food and health, including the contextual conditions of food availability, accessibility and affordability. This provides opportunities to re-embody food by contextualising it as part of natural and built environments, thus engaging with how challenges of human health intersect with animal and environmental health. The research centres on co-creating knowledge with youth based on their valued beings and doings about health and considers how their health goals relate to food and the sustainability challenges of antimicrobial resistance (AMR). By considering how youths' understandings, evaluations and decisions regarding health, including setting health goals, intersect with the determinants of food, we come to consider their health literacy capabilities to achieve nonpredetermined health goals that align with their valued beings and doings. As such, the implementation gap between knowing and doing is bridged through practices of health and well-being contextually grounded in the lives and experiences of the student youth.